Individual Treatment Effects of Budget Balance Rules. (IMF Working Papers; Working Paper ;, 2020)
This paper investigates the heterogenous effects of budget balance rules on fiscal policy in a large sample of countries. To derive country-specific treatment effects of fiscal rules and conduct inference, we use a Synthetic Difference-in-Differences Method. Our results indicate that countries with a budget balance rule improve their fiscal balance on average by around 3 percent after its introduction. However, our results also illustrate the importance of going beyond the average treatment effect, as it masks significant heterogeneity in the country-specific impact of the rule. We find that countries that would have had large deficits in the absence of the fiscal rule exhibit positive treatment effects, thus reducing their budget deficits. On the other hand, countries with budget surpluses respond to fiscal rules by reducing their budget surplus and moving closer to the numerical target of the rule. Our results also suggest that rules' design matters: a small overall number of fiscal rules, and the presence of a monitoring process outside the government, especially at the supra-national level, improve significantly the effectiveness of the rules.